Emotion and Movement with AppIHC: Promoting Interaction and Socialization Among Participants of Scientific Events via Mobile Application - Tramontin A.* (2019)
© 2019, Springer Nature Switzerland AG.Scientific events bring together a large number of researchers and are composed of different types of sessions, consisting of workshops, mini-courses, full papers, etc., with different topics. The high content diversity may cause an overload of information to attendees, making it difficult to choose between all sessions. This paper describes a mobile application called AppIHC to help attendees access event’s schedule and promote users’ engagement. Developed for the Android platform, the application has a Recommender System that uses information from the users’ profile and their interests to generate recommendation by content, and also produces social recommendations from a pre-existent database of co-authoring from previous event editions. A gamification process was applied to promote engagement between the attendees. The application was used during the event XVI Brazilian Symposium on Human Factors in Computing Systems (IHC 2017) and had 108 registered users, being evaluated through a satisfaction questionnaire and through analysis of activity records. The results indicate the goal of facilitating access to information and improving user participation in the event has been achieved.